Symbolika matematyczna związana z pojęciem funkcji - Jóźwik, Izabela; Terepeta, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
Mathematical texts are characterised by the occurrence of specificsymbols. They may be letters (as applied, for example, by Euclid), numbersymbols or graphic signs with context-independent meaning. Mathematicalsymbols store knowledge of previous generations that provides frameworkswith which to examine history of mathematical problems. In this paper, wedeal with symbols related to the concept of function and related concepts likelimit, and some other set theoretical or logical concepts. We focus on symbolsthat have survived unchanged into the present day and are commonlyused. In part, we rely on the well-known book by Florian Cajori, “Historyof Mathematical Notations”, first published in 1928-1929. Since mathematicalnotation is still growing, we also present symbols emerged after [Cajori1928-1929].